CHALLENGES OF EDUCATIONAL MANAGEMENT IN PANDEMIC REALITY (ON THE EXAMPLE OF AKAKI TSERETELI STATE UNIVERSITY) - Nana Lukhutashvili; Tea Valishvili; Lia Genelidze (ეკონომიკური პროფილი, 2022)
The pandemic has significantly adjusted global processes. The world will never be the same as it was before the pandemic. The COVID-19 challenge was met differently by countries as well as individual industries. The pandemic has emerged as a catalyst for some of the accumulated problems and shortcomings. Naturally, the changes also affected the educational field, which is one of the most sensitive sectors to economic and social change.